Kinerja Keuangan dan Return Saham Perusahaan Blue Chip di Bursa Efek Indonesia - Suryo, Ariel; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 31 No 12 (2021)DO - 10.24843/EJA.2021.v31.i12.p19, 2021)
The purpose of this study is to provide empirical evidence regarding the effect of return on assets, earnings per share, and return on equity on stock returns. This research was conducted on Blue Chip companies listed on the Indonesia Stock Exchange (IDX). The number of samples taken as many as 81 samples, with non-probability sampling method with saturated sampling technique. Data collection is done by non-participant observation. The analysis technique used is multiple linear regression technique. The results of the analysis found that return on assets, earnings per share, and return on equity had a positive effect on stock returns of Blue Chip companies listed on the IDX for the 2017-2019 period. Keywords : Stock Return; Return On Assets; Earnings Per Share; Return On Equity; Blue Chip.